Advanced In Situ Induced Dual‐Mechanism Heterointerface Towards Ultrastable Aqueous Rocking‐Chair Zinc‐Ion Batteries. Issue 41 (31st August 2022) - Cai, Peng; Wang, Kangli; Ning, Jing; He, Xin; Chen, Manlin; Li, Qixing; Li, Haomiao; Zhou, Min; Wang, Wei; Jiang, Kai
Abstract: The practical application of infancy‐stage rocking‐chair Zn‐ion batteries is predominately retarded by the strong electrostatic interaction between traditional anode materials with bivalent Zn 2+, resulting in irreversible serious structural damage, unsatisfactory cycling stabilities, and poor rate performances. Herein, an advanced dual electric field in situ induced intercalation/conversion dual‐mechanism Na1.6 TiS2 /CuSe2 heterointerface anode towards ultrastable aqueous rocking‐chair zinc‐ion batteries is successfully constructed. The rational constructions of huge heterointerfaces between different phases generate built‐in electric fields, reducing the energy barrier for ion migration, facilitating electron/ion diffusion, decreasing charge transfer resistances, and establishing an excellent conducting network. The enhanced interactions of different atoms at the phase interface alleviate the tensile strain and stabilize the lattice, achieving superior Zn 2+ diffusion kinetics. The dual‐mechanism Na1.6 TiS2 /CuSe2 heterostructures can reach a discharge capacity of 142 mAh g −1 at 0.2 A g −1 . It still reaches a discharge capacity of 133 mAh g −1 when the current density recovers to 0.2 A g −1 after a high current evaluation of 10 A g −1 with remarkable capacity retention (83.8% at 5A g −1 after 12 000 cycles). This breakthrough opens a new avenue for the targeted design of rocking‐chair zinc‐ion batteries and provides insights into the evolution of heterointerfaces. Abstract : TiS1.34 Se0.66 nanoplates spontaneously in situ generate Na1.6 TiS2 /CuSe2 heterointerfaces. This breakthrough opens a new avenue for the targeted design of rocking‐chair zinc‐ion batteries and provides insights into the evolution of heterointerfaces.